The Conflict between Somalian - Ethiopian Aboyt Al - Oaghaden 1960 - 1978 - سميرة عبد الرزاق عبد الله (College of Education for Women, 2019)
The study of the subject shows us the couflict between Somalian- Ethiopian. About Al-Oaghaden (1960-1978). This province is purely Somalian area in their language ،manners ، traditions ،and their most population from Migrant bedouin. In the last nineteenth century ،Ethiopia had entered to exit from plateau ،and become nearly from Red Sea and Indian Ocean. The study shows us ،the conflict between colonization countries ،about African horn ،then fore Ethiopia entered as partner to divide the zone area ، and that division hadn't Cares about the unity of people ،or the similar of language or religoun ،for this reason which had interference happened between broders and division about the same tribe from more Century ، and that case had appeared clearly to destroy the unity of nation in the African horn ،it was somalian nation. The military war between Somalin and Ethiopia against Oaghaden had entered to the sureness result ،about the local and internation wills. From the area ،and contradict the interests and aims. For this reason, The first military confrontion had happened in the 1964. The second in 1977.The confrontions were a practial experimented about the conflict between the great powers ، and exploited to picality powers to produce the conflict under the political compatibility between soviets- American. We can said ،that the efforts of united African organization to settlement between conflict powers by pacification efforts ،and to coutrol the fire ،and stop the issue which had helped the conflict powers to negotiatigion without the organization and without entered to the redical solution to that conflict ،It ends to rule the province from Ethiopian in 1978.